Making Questionnaire for Studying Barriers of Utilizing the Scientific Evidence in Health Care System in Islamic Republic of Iran from the View point of Decision Makers - Mohammad Zakaria Pezeshki; Hossein Jabbari; Barmak Yaaghoobian (Tabriz University of Medical Sciences, 2013)
Introduction: Inappropriate utilization of scientific evidence in health systems has led to a motivation for designing different studies by various stakeholders to identify the dimensions of this problem and the proper solution for them. In health system of Islamic republic of Iran, among the most important stakeholders are senior and middle managers whose opinions about barriers of utilization of scientific evidence can be studied by questionnaire. This study has been done to make this questionnaire and find items and sub scales with appropriate content validity. Methods: Delphi method was used in three rounds among 10 experts in the fields related to health management in the universities that had the greatest research on health system, knowledge transfer and barriers to use of scientific evidence. The basic scientific content of the questioned items was WHO report table in 2004 entitled "Knowledge for better health". Results: 75 items were obtained in 13 sub scales of which 73 items and 11 sub scales were changed or they were new. The sub scales were Health-care system, practice , educational , social and political environments, care providers, patients and their attendants, country health system, medical council and forensic medicine, research environment, economic environment, insurance and payment system and information infrastructures.Conclusion: 2 items and five subscales of the main items listed in the table of the World Health Organization remained unchanged, 21 items and 5 subscales were changed and 52 items and 6 subscales were added. All subscales in BARRIER questionnaire have equivalents in the table obtained from our study except the subscale of the quality of research indicating the problems of scientific evidence.